Functional trait effects on ecosystem stability: assembling the jigsaw puzzle - de Bello, Francesco; Lavorel, Sandra; Hallett, Lauren M; Valencia, Enrique; Garnier, Eric; Roscher, Christiane; Conti, Luisa; Galland, Thomas; Goberna, Marta; Májeková, Maria; Montesinos-Navarro, Alicia; Pausas, Juli G; et al. (Trends in ecology & evolution, 2021)
Under global change, how biological diversity and ecosystem services are maintained in time is a fundamental question. Ecologists have long argued about multiple mechanisms by which local biodiversity might control the temporal stability of ecosystem properties. Accumulating theories and empirical evidence suggest that, together with different population and community parameters, these mechanisms largely operate through differences in functional traits among organisms. We review potential trait-stability mechanisms together with underlying tests and associated metrics. We identify various trait-based components, each accounting for different stability mechanisms, that contribute to buffering, or propagating, the effect of environmental fluctuations on ecosystem functioning. This comprehensive picture, obtained by combining different puzzle pieces of trait-stability effects, will guide future empirical and modeling investigations.
Keywords: Biodiversity; insurance effect; ekosystém; functional diversity and redundancy; biodiverzita; fenotyp; Phenotype; trait probability density; community weighted mean; Ecosystem; compensatory dynamics